Avaliação fisioterapêutica em indivíduos com apneia obstrutiva do sono segundo os conceitos relacionados à funcionalidade: qual a prática atual no Brasil? - Santos, Jefferson Nascimento dos (2024)
Obstructive Sleep Apnea (OSA) is one of the most prevalent sleep disorders, affecting approximately 1 billion individuals aged 30-69 worldwide. It is a disease that can be quite disabling, impacting body functions and structures and limiting individuals' activities and participation. By understanding the damage resulting from OSA, the need to employ appropriate physiotherapeutic assessments to extract meaningful data that can guide interventions respecting the individuality of the patient and consequently be more assertive in promoting functioning becomes evident. Therefore, the objective was to investigate the use of the functioning model through the International Classification of Functioning, Disability and Health (ICF) in the evaluation carried out by physiotherapists in individuals with OSA. The study was conducted as an electronic survey, answered by Brazilian physiotherapists working in the field of sleep, with items related to physiotherapeutic assessment practices, sociodemographic, and academic characteristics. The Wilcoxon test was adopted for comparison between the ICF codes when indicating their applicability during assessment and as an objective for physiotherapeutic treatment. Qualitative data were analyzed using thematic analysis, and the word cloud technique was used complementarily for information processing. After responding to a virtual questionnaire, it was identified that 62.5% of the professionals work exclusively in clinical care with sleep disorders, 43.1% are certified in sleep, and there is a greater presence of physiotherapists in the southeast region of the country with 40 professionals. The components of the functioning model are seen as relevant during the evaluation routine, with emphasis on the activity component, indicated as the most relevant. The practice of frequently assessing functioning was indicated by 86.1% of the respondents. When comparing physiotherapists certified in sleep with those not certified, the results showed that 93% of the certified group and 80% of the non-certified group assessed functioning before therapeutic interventions as an outcome; however, this practice is often carried out through open questioning of the patient rather than validated instruments for this purpose. In summary, physiotherapists in Brazil recognize functioning as an outcome measure and investigate its components; however, the components of body function and activity are emphasized in this process. Furthermore, subjective questions are frequently adopted as an evaluative tool to measure functioning, but this approach does not encompass the biopsychosocial model. Regarding perception, it is noted that professionals, regardless of the group (certified or not certified), associate functioning with the performance of daily activities. These studies provide information for the gap in scientific literature that had not yet described the application of the functioning model in the clinical practice of sleep physiotherapy specifically in the evaluation practice. These data enable reflection on the importance of adopting functioning as a guiding axis of physiotherapeutic clinical practice and how this has been applied in the context of assistance to patients with OSA. With this discussion, it is hoped to contribute to the improvement of the assistance offered to this population.